Peran Balai Pemuda Dan Olahraga Yogyakarta Dalam Upaya Pengembangan Kewirausahaan Pemuda Untuk Mendukung Ketahanan Ekonomi Keluarga ( Studi Tentang Persepsi Peserta Kegiatan Pelatihan Keterampilan BPO DIY) - Muhammad Iskandar Zulkarnain (Jurnal Ketahanan Nasional, 2015)
ABSTRACTThis research aimed to analyzed the programs and activities proposed by the Center for Youth and Sports in the Province of Yogyakarta Special Region in  promoting entrepreneurship among the youth, and to analyzed  as well as the aspect of the family economic resilience of the participants attending the catfish farming training program held by the Center for Youth and Sports in the Province of Yogyakarta Special Region.The method employed was the combined method of descriptive qualitative methods and quantitative methods by conducting observation, structured interviews and library research. For assessing the roles of the Center for Youth and Sports in the Province of Yogyakarta Special Region in promoting entrepreneurship among the youth, was used  7 standards of entrepreneurship promotion efforts among the youth according to the Government Regulation No. 41/  2011,  while to assessed  the family economic resilience of the participants attending the skill training program held by the Center for Youth and Sports in the Province of Yogyakarta Special Region were used the data on the income generated by each participants that were met with the standard minimum wage for cities/ regencies.The result of the research showed that the seven aspects of the entrepreneurship promotion efforts among the youth, the Center for Youth and Sports in the Province of Yogyakarta Special Region were considered to played  roles in the aspects of training and internship, while for the aspects of guidance, assistance, partnership and promotion were  considered not performing its roles. Finally, for the aspects of capital assistance and access, its roles in these aspects were considered not optimal. It was based the fact that the Center for Youth and Sports in the Province of Yogyakarta Special Region had not  managed to established a capital institution which helped to provided the funds for the purpose of promoting entrepreneurship among the youth even though the Center for Youth and Sports at the central level had already provided the initial capital assistance for the cadre of young entrepreneurs. ABSTRAKTujuan penelitian ini untuk menganalisis Program dan Kegiatan yang disusun oleh  Balai Pemuda dan Olahraga Provinsi DIY dalam upaya pengembangan kewirausahaan pemuda, kemudian untuk menganalisis peran Balai Pemuda dan Olahraga Provinsi DIY dalam upaya pengembangan kewirausahaan pemuda dan yang terakhir untuk menganalisis aspek ketahanan ekonomi keluarga para alumni kegiatan pelatihan keterampilan budidaya lele yang digagas oleh Balai pemuda dan Olahraga Provinsi DIY. Metode yang digunakan yakni metode penggabungan antara metode deskriftif kualitatif dan metode kuantitatif, dengan menggunakan observasi, wawancara terstruktur dan studi pustaka. Untuk mengukur peran Balai Pemuda dan Olahraga Provinsi DIY dalam upaya pengembangan kewirausahaan pemuda digunakan 7 standar pengembangan kewirausahaan pemuda menurut Peraturan Pemerintah Nomor 41 tahun 2011,  selain itu guna mengukur ketahanan ekonomi keluarga alumni kegiatan pelatihan keterampilan yang diselenggarakan Balai Pemuda dan Olahraga Provinsi DIY digunakan data pendapatan para alumni yang dicocokkan  dengan standar upah minimum kabupaten.Hasil penelitian menunjukkan bahwa  7 (tujuh) aspek pengembangan kewirausahaan pemuda, BPO Provinsi DIY telah dinilai berperan pada aspek pelatihan dan pemagangan, namun pada aspek pembimbingan, pendampingan, kemitraan dan promosi dinilai bahwa BPO Provinsi DIY belum menjalankan perannya, sementara itu untuk aspek bantuan dan akses permodalan BPO provinsi DIY dinilai belum sepenuhnya berperan. Hal ini didasarkan fakta bahwa BPO Provinsi DIY belum berhasil membentuk lembaga permodalan kewirausahaan pemuda meskipun BPO sudah memberikan bantuan permodalan awal bagi kader wirausahawan muda